1995
DOI: 10.1002/hep.1840220441
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene expression by Kupffer cells in experimental alcoholic liver disease

Abstract: Kupffer cell-derived cytokines are believed to play pivotal paracrine roles in the pathogenesis of alcoholic liver disease (ALD). To evaluate this hypothesis, Kupffer cell gene expression of tumor necrosis factor-alpha ( m a ) , interleukin (IL)-6, and transforming growth factor-beta 1 (TGFP1) were directly examined in the rat model of ALD. Kupffer cells were isolated from the model after 10 and 17 weeks of intragastric ethanol infusion. These two durations resulted in focal hepatocellular injury and liver fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
111
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 34 publications
6
111
1
Order By: Relevance
“…Rats chronically fed ethanol were more sensitive to the hepatotoxic effects of administration of LPS and had higher plasma levels of TNFα than control rats (196)(197)(198). In the intragastric model of chronic ethanol administration, the development of liver injury coincided with an increase in TNFα, associated with an increase in serum LPS (195,(197)(198)(199). The pioneering studies of Thurman and collaborators showed that anti-TNFα antibody prevented alcohol liver injury in rats (200) and mice lacking the TNFR1 receptor did not develop alcohol liver injury (133).…”
Section: Lps/tnfα-cyp2e1 Interactionsmentioning
confidence: 99%
“…Rats chronically fed ethanol were more sensitive to the hepatotoxic effects of administration of LPS and had higher plasma levels of TNFα than control rats (196)(197)(198). In the intragastric model of chronic ethanol administration, the development of liver injury coincided with an increase in TNFα, associated with an increase in serum LPS (195,(197)(198)(199). The pioneering studies of Thurman and collaborators showed that anti-TNFα antibody prevented alcohol liver injury in rats (200) and mice lacking the TNFR1 receptor did not develop alcohol liver injury (133).…”
Section: Lps/tnfα-cyp2e1 Interactionsmentioning
confidence: 99%
“…Both proinflammatory and anti-inflammatory as well as growth regulatory properties have been described. 54 Evidence has been presented for an involvement of Kupffer cell-mediated TGF-␤ 1 activation in alcohol-induced liver fibrosis 16 and TGF-␤ 1 expression in liver biopsy specimens from patients with liver disease and in experimental ALD has been reported. 55,17 In the present study TGF-␤ 1 mRNA expression was significantly increased by chronic ethanol treatment, but histologically no signs of changes related to fibrosis could yet be seen.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…[13][14][15] Chronic intragastric ethanol feeding increases the expression of Kupffer cell cytokine messenger RNAs (mRNAs) for TNF-␣, interleukin 6 (IL-6), and transforming growth factor ␤ 1 (TGF-␤ 1 ). 16,17 Peripheral blood monocytes isolated from ALD patients secrete higher levels of TNF-␣ than monocytes from control subjects. 18 In patients with various liver diseases, serum concentrations of proinflammatory cytokines TNF-␣, IL-1, and IL-6 are elevated.…”
mentioning
confidence: 99%
“…[10][11][12] A third mechanism by which ethanol induces liver fibrosis is that related to the increased expression of cytokines after liver injury and/or the inflammatory response of the injured tissue. 13,14 Of these, it has been already established that transforming growth factor ␤1 (TGF-␤1) and interleukin 6 are fibrogenic. 15,16 Additional mechanisms could include those related directly or indirectly to the production of adducts between acetaldehyde and/or malondialdehyde and specific proteins.…”
mentioning
confidence: 99%